Pullout behaviour of ribbed bars in self-compacting concrete with steel fibers. (2021) - Majain, Nelly; Rahman, Ahmad Baharuddin Abdul; Adnan, Azlan; Mohamed, Roslli Noor
Abstract: This research mainly focuses on the pullout behaviour of different ribbed bars size embedded in plain Self-Compacting Concrete (SCC) and also in SCC with Steel Fibers (SCCSF). The diameter of the ribbed bars was 12, 16 and 20 mm. The steel fibers used in this study were the hooked end type with 35 mm length and an aspect ratio of 63.6. This study attempts to investigate factors influencing the pullout behaviour by using the embedment length recommended by RILEM RC6 Part 2 which is 5 times the bar diameter using the direct pullout test method. A total of 9 specimens with a dimension of 200 mm cube were prepared and tested. It was found that the proposed embedment length was large for 12 and 20 mm diameter bars but fitting for bond stress investigation with the 16 mm diameter bar. The addition of steel fibers in SCC improves the compressive and tensile strengths of SCCSF and provides concrete confinement that enhances the bond between ribbed bars and the surrounding concrete. Besides, the presence of steel fibers also changes the failure mode of SCCSF specimens especially with 20 mm diameter rebars in which the failure mode changes from premature splitting to pullout.